Transportable Seismic Discriminants: The Use of Cross-Spectral Measurements to Reduce Parameter Scatter and Identification Error - Pulli, Jay J. (1995)
Much progress has been made in regional seismic discrimination over the past ten years. Aided by the availability of high-quality waveforms and ground-truth databases, researchers discovered the discrimination capabilities of Lg/P and S/P spectral ratios, especially at high frequencies. However, when spectral ratios or signal parameters which perform well in one geographic area are applied to events in another, the results are typically uncertain or erroneous. This was illustrated during the identification analysis of the Dec. 31, 1992 Novaya Zemlya event: the same data were analyzed by a number of researchers who came to uncertain or conflicting conclusions. For regional discrimination to work in a CTBT context, this problem must be overcome. The most obvious factors contributing to transportability failure include geographic variability of source and path effects. However, noise and the inherent instability of spectral ratio calculations at low SNR's and restricted bandwidths are also likely factors. Regional seismic spectra rarely follow the model of a flat low-frequency spectrum with smooth high-frequency rolloff. This is especially true for quarry explosions, where long time-delay ripple firing can add harmonic distortion. Good signal processing practice dictates that measurements be made only at frequencies where there is sufficient SNR, which often means the use of cross spectral and system identification methods. This project will extend the discrimination research conducted to date to include these methods. This article is from 'Proceedings of the Annual Seismic Research Symposium on Monitoring a Comprehensive Test Ban Treaty (17th) Held in Scottsdale, Arizona on 12-15 September, 1995', 1996 0607 035, p90-97.